Sistema híbrido eletroquímico–fotoquímico para a mineralização do herbicida tebutiuron - Sánchez Montes, Isaac José (2016)
An electrochemical-photochemical system (EC-PC) using a dimensionally stable anode (DSA®) was used to oxidize and mineralize tebuthiuron (TBT) herbicide, which is a potential contaminant to the surface and ground water. The electrochemical process was conducted using a filter-press flow cell and the photochemical one by irradiation of the solution inside the reservoir using Hg vapor lamps (type UVC). The studied variables were: i) nominal power of Hg lamps (5, 9, 80, and 125 W), ii) pH (3, 7, 11, and no control), iii) NaCl concentration (0, 1, 2, and 4 g L–1), and iv) current density (10, 20, and 30 mA cm–2). Other parameters were kept constant, such as the flow rate (420 L h–1) and the solution temperature (25 °C). The electrolyzed solution was composed of 100 mg L–1 TBT and 0.1 mol L–1 Na2SO4, as supporting electrolyte. The oxidation and mineralization performances of the TBT and its intermediates using the hybrid process were assessed through high performance liquid chromatography coupled to mass spectrometry (HPLC-MS/MS), depending on the experiment, and total organic carbon (TOC) analyses. The experiment using a 9 W Hg lamp led to the complete oxidation and mineralization of TBT and its intermediate compounds in the presence of NaCl from acidic to neutral solutions, including the one with no control, and independently of the applied electrical current density. High CO2 conversions were attained after 6 h using the combined EC-PC process, due to the generation of hydroxyl radicals (HO•) from HOCl homolysis. The HO• also favored the formation of many hydroxylated organic compounds. Despite the formation of an organochlorine byproduct, this compound was completely eliminated after 3 h treatment. Moreover, no toxicity was observed when using the Artemia salina microcrustacean. Similar removal rates of TBT were attained when only using an electrochemical method with boron-doped diamond as anode. In addition, the EC-PC process showed a slightly higher electrical energy consumption for the removal of organic matter in comparison to the electrochemical one. Finally, only a chlorinated carboxylic acid was detected; however, this compound was completely eliminated in the final stages of the EC-PC treatment. All these features enables the classification of this method as an advanced oxidation process.